2012
DOI: 10.1140/epjc/s10052-012-2164-1
|View full text |Cite
|
Sign up to set email alerts
|

Study of the inclusive production of charged pions, kaons, and protons in pp collisions at $\sqrt{s} = 0.9, 2.76,\mbox{ and }7~\mbox{TeV}$

Abstract: Spectra of identified charged hadrons are measured in pp collisions at the LHC for √ s = 0.9, 2.76, and 7 TeV. Charged pions, kaons, and protons in the transversemomentum range p T ≈ 0.1-1.7 GeV/c and for rapidities |y| < 1 are identified via their energy loss in the CMS silicon tracker. The average p T increases rapidly with the mass of the hadron and the event charged-particle multiplicity, independently of the center-of-mass energy. The fully corrected p T spectra and integrated yields are compared to vario… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
161
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 177 publications
(170 citation statements)
references
References 115 publications
6
161
0
3
Order By: Relevance
“…By using Equations (15), (17), and (18)- (20), together with the definitions in Equation (13) in the considered collisions, the abundances of particle and antiparticle are approximately equal to each other [3]. This can be clearly seen in Figure 1.…”
Section: The Thermal Motion Induced Transverse Momentum Distributionsmentioning
confidence: 78%
See 2 more Smart Citations
“…By using Equations (15), (17), and (18)- (20), together with the definitions in Equation (13) in the considered collisions, the abundances of particle and antiparticle are approximately equal to each other [3]. This can be clearly seen in Figure 1.…”
Section: The Thermal Motion Induced Transverse Momentum Distributionsmentioning
confidence: 78%
“…In the past decades, a number of bulk observables about charged particles, such as the Fourier coefficients n v of azimuth-angle distributions [1] [2], transverse momentum spectra [3]- [8] and pseudorapidity distributions [9] [10], have experienced a series of extensive investigations in both nucleus and hadron collisions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have also observed that in pp collisions at LHC energies [3,4], the characteristics of particle production ( p T , ratios of yields) are strongly correlated with the particle multiplicity in the event, which is in itself closely related to the number of underlying parton-parton interactions, independently of the concrete center-of-mass energy of the pp collision.…”
Section: Multiplicity-dependent Measurementsmentioning
confidence: 95%
“…The analysis adopts the same methods as used in previous CMS measurements of pion, kaon, and proton production in pp and pPb collisions at √ s of 0.9, 2.76, and 7 TeV [3,4], as well as those performed by the ALICE collaboration at 2.76 and 7 TeV [5,6]. Further details of the analysis are given in Ref.…”
Section: Introductionmentioning
confidence: 99%